2009
DOI: 10.1007/s11255-009-9523-3
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence among Taiwanese women: an outpatient study of prevalence, comorbidity, risk factors, and quality of life

Abstract: The objective of this study was to evaluate comorbidity and risk factors associated with female urinary incontinence and to assess quality of life for women with different types of urinary incontinence. Subjects included 551 consecutive females who attended the outpatient clinic from 9 March to 8 July 2006 and did not have a chief complaint of incontinence. A four-item incontinence questionnaire and a Chinese version of the Incontinence-Quality of Life (I-QOL) questionnaire were completed in the waiting room. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 39 publications
7
50
0
Order By: Relevance
“…Sample Size estimated after doing a thorough Review of Literature where it was found that the prevalence ranges from 0-60%. [6][7][8][9][10][20][21][22][23][24] Taking a mean prevalence as 30%, relative error of 20% of p. Using Formula: N = z²pq/L², we got the sample size as 233. Taking design effect of 2 and applying non-response rate of 5 %, we finally took a sample size of 530 postmenopausal women.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample Size estimated after doing a thorough Review of Literature where it was found that the prevalence ranges from 0-60%. [6][7][8][9][10][20][21][22][23][24] Taking a mean prevalence as 30%, relative error of 20% of p. Using Formula: N = z²pq/L², we got the sample size as 233. Taking design effect of 2 and applying non-response rate of 5 %, we finally took a sample size of 530 postmenopausal women.…”
Section: Methodsmentioning
confidence: 99%
“…20 Although interest is growing in the investigation, treatment, and management of incontinence, its prevalence in the general population has so far been based on estimates made in selected groups of people of different ages. 21 Therefore, the following study was carried out with the two objectives; one is to find out the effect of menopause on the occurrence of Urinary Incontinence in women and second is to find out risk factors in post-menopausal women associated with Urinary Incontinence.…”
Section: Types Of Uimentioning
confidence: 99%
See 1 more Smart Citation
“…7 -10 The increase in incontinence with advancing age is thought to be due to impairment of the urethral muscle structure, characterized by reduction in the number of striated muscle fibres in the anterior wall of the urethra. 19 Urinary stress incontinence was reported to be 6.24-fold more common among women aged ≥ 65 years than those aged 15 -24 years, 20 …”
Section: Discussionmentioning
confidence: 99%
“…Increased BMI is associated with increased intra-abdominal pressure, thereby straining pelvic floor structures and increasing bladder pressure and urethral mobility. The physiopathology of UI is related to compromise of the levator (24).…”
Section: Mizaj In Sui Womenmentioning
confidence: 99%